Eco-Theological Community-Based Waste Management For Sustainable Mangrove Ecosystem Conservation In Sinjai Regency - Hardiyanti Ridwan; Srianti Permata; Ibrahim Abdullah; Zaenal Abidin; Satria Ramli; Isma Nawaitul Ihram; Jusrifal Maulana Putra (Masterpiece, 2026)
Mangrove ecosystems play a vital role in maintaining coastal environmental balance, protecting shorelines from erosion, sequestering carbon, and supporting local economic activities. However, the mangrove area in Tongke-Tongke Village, Sinjai Regency, faces ongoing issues with pollution specifically plastic and household waste that threaten the sustainability of its ecological functions and tourism potential. Consequently, a Community Partnership Program (PKM) titled "Eco-Theological Community-Based Waste Management for Sustainable Mangrove Ecosystem Conservation in Sinjai Regency" was implemented to establish a community-based waste management model integrated with Islamic eco-theological values. The program employed Participatory Community Development, Community-Based Waste Management (CBWM), and eco-theological approaches, progressing through stages of problem identification, environmental education, internalization of Islamic eco-theological values, implementation of conservation actions, and activity evaluation. Target participants included coastal residents, the Tourism Awareness Group (Pokdarwis), religious leaders, youth, women, and mangrove tourism managers. Results indicated an increase in community knowledge and awareness regarding waste management and mangrove conservation. Internalizing values ​​such as khalīfah fī al-arḍ (stewardship of the earth), amānah (trust/responsibility), mīzān (balance), and maṣlaḥah (public interest) strengthened the community's moral and spiritual commitment to environmental stewardship. The program also successfully boosted community participation in mangrove cleanup drives and waste sorting, and established a "Mangrove-Caring Community Group" as a local institution to ensure the program's long-term sustainability. Overall, the approach integrating community-based waste management with Islamic eco-theology proved effective in supporting sustainable mangrove conservation in Tongke-Tongke Village.